A new species of Arctodiamesa Makarchenko (Diptera: Chironomidae: Diamesinae) from the Russian Far East, with a key to known species of the genus - Makarchenko, Eugenyi A. (Zootaxa, 2005)
The male, pupa, and larva of a new species, Arctodiamesa marinae, from the Russian Far East are described and figured. Keys to males, pupae, and fourth-instar larvae of known species of the genus are presented.